Breaking organizational routines as a requirement for knowledge broker’s leadership role - Janiszewski, Adam (Видавництво Львівської політехніки, 2017)
In the paper based on conclusions stemming from literature connected with organizational knowledge creation, territorial innovation models as well as knowledge intermediaries author tries to build hypothesis relating to the possibility of changing ways of both performing tasks and achieving goals. It is proposed that such kind of opportunity is related to the nature of the projects under realization reflected by the type of learning that occurs
Keywords: knowledge brokers; types of learning; leadership